Artificial Intelligence and Forensic Sciences: A Bibliometric Analysis of Publications - Aydoğdu, Halil İlhan (The Bulletin of Legal Medicine, 2023)
Objective: Forensic science is a superstructure that encompasses many specialized fields that require expertise. In recent years, studies have been conducted on artificial intelligence and machine learning-based applications in almost all areas of forensic science. The aim of our study is to determine the trends related to the research/application areas of artificial intelligence and machine learning-based programs in forensic sciences and to make predictions about the future of the subject, and to contribute to the professionals working in the field.Methods: When the Web of Science database was searched with the keywords “artificial intelligence/machine learning” and “forensic/forensic science” in the title or abstract between 2001-2023, 229 results were obtained. Simple frequency analyses were performed using IBM SPSS 23 software for the study, and R Studio and Vosviewer (version1.16.19) programs were used for bibliometric analysis.Results: It was found that there were 229 publications meeting the criteria, and the most studies on the subject were published in International Journal of Legal Medicine with 9 publications. The most frequently published countries were the United States with 32 (13.9%) publications, China with 30 (13.04%) publications, and India with 23 (10%) publications. The most commonly used keywords in the publications were “artificial intelligence”, “deep learning” and “machine learning”. Conclusion: The results of analysis show that artificial intelligence and machine learning-based systems have become increasingly studied in many areas of forensic science in recent years. As machine learning/artificial intelligence programs are developed, it is likely that these applications will be used in forensic science/medicine practice.
Keywords: Artificial Intelligence; Machine Learning; Forensic Sciences; Bibliometric Analysis